Studi Komparatif Peran Orang Tua terhadap Perilaku Pencegahan Kekerasan Seksual pada Anak Usia Sekolah antara SMAN 1 & SMAN 3 Kota Kendari Tahun 2024 - Adelia Putri Rahayu; Sartiah Yusran; Fifi Nirmala (Jurnal Ventilator, 2025)
Cases of Sexual Violence in Southeast Sulawesi have been increasing from year to year, in Kendari City recorded cases of violence against women and children in the year 2022 from January 2022 to December 2022 as many as 40 cases. There were 38 cases in 2021, while in 2022 there were 40 cases. This research aims to find out the difference in the role of parents in the prevention of sexual violence in school age children between SMAN 1 Kendari and SMAN 3 Kendari. This research uses a cross sectional study design. The population in this research is all 2nd and 3rd grade students who are 758 people in SMAN 1 and 746 people in SMAN 3 in Kendari City. The sample in this research is 85 students of SMAN I Kendari and 85 students of SMAN 3 Kendari, sampling using the proportional random sampling technique using the Mann-Whitney test. Obtained the results of the research by comparing between SMAN 1 & SMAN 3 Kendari City, it is seen that there is no significant difference in the role of parents as counselors, the value of p = 0.134 is found, and there is a significant difference in the role of parents as caregivers, the value of p = 0.000 is found. This research is expected to indicate the importance of the role of parents as a key factor in creating a safe and supportive environment for PKS in children.